Basic medical record education and training to prepare professional health human resources - Asmi, A Syamsinar; Ihsan Kamaruddin, Muh; Ode Novi Angraeni, Wa; Hardi, Wahyudi; Andre Mangaya Takke, Jessy (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2025)
Accurate and well-managed medical records are crucial for ensuring the quality of health services, supporting informed clinical decision-making, and enhancing health information systems. However, many health workers especially those in primary care and early-career stages lack adequate competence in basic medical record management. This community service program aimed to enhance participants’ knowledge and skills in fundamental medical record practices as part of preparing professional and reliable health human resources. This program was conducted through a structured educational and training intervention involving a one-day workshop delivered to 45 health workers and students. Activities included lectures, demonstrations, hands-on practice, and group discussions. Pre- and post-training assessments were used to measure improvements in knowledge and practical skills. Observational checklists evaluated participants’ accuracy in completing medical record components, including patient identification, documentation standards, coding basics, and confidentiality procedures. The results showed a significant improvement in participants’ understanding and performance. The mean knowledge score increased from 62.4 (pre-test) to 88.7 (post-test). Practical skills in completing standardized medical record forms improved from 54% to 90% accuracy. Participants reported increased confidence in maintaining documentation quality and understanding the legal and ethical responsibilities related to medical records. Feedback indicated high satisfaction with training methods and relevance to daily practice. This community service program effectively strengthened the foundational competencies required for health workers to manage medical records professionally. The combination of theory and practical sessions proved essential in building both conceptual understanding and hands-on skills. Continuous training and mentoring are recommended to ensure sustained quality and compliance with health information standards